The multi-scalar embeddedness of support policies for migrant entrepreneurship in Japan - Sakura Yamamura (International Migration, 2022)
Contextual entrepreneurship and mixed embeddedness approach alike emphasize the importance of the political-institutional embeddedness next to social embeddedness along with further contexts for migrant entrepreneurship, yet the aspect of international migration policies as an important institutional framework has been somewhat neglected. This paper introduces the case of political-institutional embeddedness of migrant entrepreneurship in Japan from an international migration policy perspective, discussing embeddedness of migrant entrepreneurs and their support institutions from a multi-scalar perspective. By analysing the migration policy context of migrant entrepreneurship at different policy levels, that is, national, regional and urban scales, it demonstrates the analytical value of differentiating policies along these scales and also their inter-connectedness, conceptually proposing the inter- and trans-scalarity of these policy contexts. By bringing issues of migration regimes and particularly the East Asian developmental state as a lens to analyse migrant entrepreneurship, it brings further approaches in comparatively analysing different entrepreneurial contexts for future research.
Keywords: 300